Effect of environmental uncertainties on the relationship of entrepreneurial orientation and business success: child care centres in Malaysia - Tan, Hong Hooi (2018)
The main objective of this study is to examine the moderating role of environmental uncertainties on the relationships between entrepreneurial orientation (EO) and business success of child care centres in Malaysia. Data were collected from a sample of child care centres operating in the whole Malaysia using a quantitative survey design. The study adopted a cluster sampling approach. The respondents were the owners of the child care centre selected from the population of 3.490 child care centres in Malaysia. Questionnaires were distributed through the postal method and online survey method. A total of 117 usable questionnaires were returned, giving a response rate of 29.7%. Partial Least Squares-Structural Equation Modeling (PLSSEM) was used to test the study hypotheses. The findings revealed that entrepreneurial orientations are important strategic orientations for the business success of child care centres in Malaysia. It further shows that innovati veness and pro-acti veness positi vely influence the business success of the child care centre. However. there is no relationship between risk-taking and the business success of the child care center. For the moderating effect, perceived environmental uncertainties were found to moderate the relationship between innovativeness and business success, but does not moderate the relationship between risk-taking, pro-activeness and the business success of child care centre. The findings of this study provide important insights to owner/managers of child care centres in Malaysia, policy makers and researchers to further understand the effects of EO on performance of child care centres in Malaysia. Owner in the child care centres in Malaysia should also be encouraged to i111prove their entrepreneur orientation which may increase their performances. Finally, the studys implications, limitations as well suggestions for future research are discussed.